Оптимизация скорости загрузки web-приложения - Кравец, М. В.; Чурсина, Т. С. (ХНУРЕ, 2019)
Web development is one of the leading software development industries. One of the most important indicators of a web resource is page loading speed. It can directly influence the popularity of a web resource and, accordingly, the prospects for its further development. The purpose of this work is to investigate the indicators of page loading speed, to study the reasons for reducing the loading speed, as well as to investigate already known approaches and develop methods for optimizing a web application to increase it.